Exigências nutricionais de caprinos da raça alpina em crescimento. 3. exigências nutricionais de energia, proteína, cálcio e fósforo1 - Sousa, HMH; de Queiroz, A. C.; Resende, Kleber Tomás de [UNESP]; da Silva, JFC; Pereira, J. C.; de Gouveia, L. J. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
This experiment was conducted to estimate the energy, protein, calcium, and phosphorus requirements for kid goats in the growing phase. Fifteen four-month-old male kid goats, average live weight of 20 kg and fed an isocaloric and isoprotein diet with increased levels of calcium, were used. The experimental period was 27 days. The animals were slaughtered to determine body composition and to estimate the body contents of energy, protein, ether extract, calcium, and phosphorus. The estimates per kg of gain were: net energy, 1,802 to 1,632 kcal; net protein, 0.168 to 0.183 g; calcium, 6.993 to 6.758 mg; and phosphorus, 5.865 to 6.430 mg for animals from 18 to 26 kg of live weight.
Nutritional requirements of Alpina breed goats in the growing phase. 3. Nutritional requirements for protein, energy, calcium, and phosphorus
Keywords: calcium; goats; growth; energy; nutritional requirements; Phosphorus; fat; protein